Dynamic genetic regulation of CD4+ T cells in obstructive sleep apnea: integrating context-specific eQTL, Mendelian randomization, single-cell sequencing, and experimental validation - Zhang, Xinyue; Ren, Lingfei (Frontiers in Immunology, 2025)
ObjectiveTo investigate the dynamic genetic regulatory mechanisms of CD4+ T cells in the pathogenesis of obstructive sleep apnea (OSA), particularly in the immune and inflammatory response induced by intermittent hypoxia (IH).MethodsThis study integrated context-specific expression quantitative trait locus analysis, Mendelian randomization, colocalization analysis, single-cell RNA sequencing, and qPCR experimental validation. A systematic investigation was conducted on gene expression and genetic variation in CD4+ T cells obtained from 119 donors of European descent across multiple activation time points including zero hours, sixteen hours, forty hours, and five days. Functional validation was performed using an IH mouse model.ResultsThe study identified multiple genes demonstrating a causal relationship with OSA risk, such as MAST3, FNBP4, SPNS1, and AKIRIN1. Thirteen expression quantitative trait loci showed significant colocalization with OSA genome-wide association study signals, with a posterior probability of shared causal variants exceeding zero point eight five. Experimental validation in the IH mouse model demonstrated significantly upregulated mRNA expression levels of Fnbp4 and Mast3, alongside downregulated expression of Sgf29, Sh3yl1, and Tufm within CD4+ T cells.ConclusionThe immune regulation mediated by CD4+ T cells demonstrates significant temporal dynamics and cell type specificity in OSA pathogenesis. Key genes including TUFM, MAST3, FNBP4, SGF29, and SH3YL1 participate in the pathological process by regulating mitochondrial function, cell migration, transcriptional regulation, and inflammatory responses. These findings provide a novel theoretical foundation and reveal potential targets for personalized therapeutic strategies and biomarker development in OSA.